Energetics and Energy Loss in 2D Ruddlesden–Popper Perovskite Solar Cells. Issue 23 (12th May 2020) - Yang, Jianming; Xiong, Shaobing; Song, Jingnan; Wu, Hongbo; Zeng, Yihan; Lu, Linyang; Shen, Kongchao; Hao, Tianyu; Ma, Zaifei; Liu, Feng; Duan, Chungang; Fahlman, Mats; et al.
Abstract: 2D Ruddlesden–Popper perovskites (RPPs) are emerging as potential challengers to their 3D counterpart due to superior stability and competitive efficiency. However, the fundamental questions on energetics of the 2D RPPs are not well understood. Here, the energetics at (PEA)2 (MA) n −1 Pb n I3 n +1 /[6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) interfaces with varying n values of 1, 3, 5, 40, and ∞ are systematically investigated. It is found that n–n junctions form at the 2D RPP interfaces ( n = 3, 5, and 40), instead of p–n junctions in the pure 2D and 3D scenarios ( n = 1 and ∞). The potential gradient across phenethylammonium iodide ligands that significantly decreases surface work function, promotes separation of the photogenerated charge carriers with electron transferring from perovskite crystal to ligand at the interface, reducing charge recombination, which contributes to the smallest energy loss and the highest open‐circuit voltage ( V oc ) in the perovskite solar cells (PSCs) based on the 2D RPP ( n = 5)/PCBM. The mechanism is further verified by inserting a thin 2D RPP capping layer between pure 3D perovskite and PCBM in PSCs, causing the V oc to evidently increase by 94 mV. Capacitance–voltage measurements with Mott–Schottky analysis demonstrate that such V oc improvement is attributed to the enhanced potential at the interface. Abstract : Interface energetics in 2D Ruddlesden–Popper perovskite solar cells are systematically investigated. The potential gradient across ligands that significantly decreases surface work function, promotes separation of the photogenerated charge carriers with electron transferring from perovskite crystal to ligand at the interface, suppressing the charge recombination and thus enhancing the open‐circuit voltage.